A Comparative Welfare Regime Approach to Global Social Policy (2021)
Beginning from the framework of welfare state regimes in rich capitalist countries, this article radically redefines it and applies the new model to regions and countries which experience problematic states as well as imperfect markets. A broader, comparative typology of regimes (welfare state, informal security, insecurity) is proposed, which captures the essential relationships between social and cultural conditions, institutional performance, welfare outcomes, and path dependence. Using this model, different regions of the world (East Asia, South Asia, Latin America, and sub-Saharan Africa) are compared. For many poorer, partially capitalized societies, people’s security relies informally upon various clientelist relationships. Formalizing rights to security via strategies for declientelization becomes a stepping stone to protecting people against the insecurity of markets.